2000
DOI: 10.1094/pdis.2000.84.6.675
|View full text |Cite
|
Sign up to set email alerts
|

Early Symptom Development and Histological Changes Associated with Migration of Bursaphelenchus xylophilus in Seedling Tissues of Pinus thunbergii

Abstract: In order to clarify the mechanism of pine wilt caused by the pinewood nematode (PWN), Bursaphelenchus xylophilus, nematode migration in tissues and disease symptoms in Pinus thunbergii seedlings were investigated. One-year-old seedlings were inoculated with different pathogenic isolates of PWN under two different temperatures. At an early stage of symptom development, a virulent isolate of PWN multiplied in both bark and xylem and was distributed in cortical resin canals, cortical tissue, and xylem resin canal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
94
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 8 publications
2
94
1
Order By: Relevance
“…In this phase, xylem embolism and tracheid occlusion occur (Kuroda, 1991). Because the nematode itself rarely enters into the tracheids of living pine (Ichihara et al, 2000), some researchers have attributed the abrupt increase in embolized tracheids to modification of the surface tension of xylem sap (Ikeda and Kiyohara, 1995), cellulase production of PWN (Odani et al, 1985), released oily substance occluding the tracheid lumen and pit membrane (Nobuchi et al, 1984;Hara and Futai, 2001), and abnormal leaks of oleoresin from resin canals (Sasaki et al, 1984). In addition, some researchers have suggested that some compounds, such as terpenoids released from parenchyma cells (Kuroda, 1989(Kuroda, , 1991 and ethylene produced in xylem (Fukuda, 1997), can induce xylem embolism, based on the results of artificial injection of these compounds into the stem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this phase, xylem embolism and tracheid occlusion occur (Kuroda, 1991). Because the nematode itself rarely enters into the tracheids of living pine (Ichihara et al, 2000), some researchers have attributed the abrupt increase in embolized tracheids to modification of the surface tension of xylem sap (Ikeda and Kiyohara, 1995), cellulase production of PWN (Odani et al, 1985), released oily substance occluding the tracheid lumen and pit membrane (Nobuchi et al, 1984;Hara and Futai, 2001), and abnormal leaks of oleoresin from resin canals (Sasaki et al, 1984). In addition, some researchers have suggested that some compounds, such as terpenoids released from parenchyma cells (Kuroda, 1989(Kuroda, , 1991 and ethylene produced in xylem (Fukuda, 1997), can induce xylem embolism, based on the results of artificial injection of these compounds into the stem.…”
Section: Discussionmentioning
confidence: 99%
“…In living pine trees, PWN rarely invade the xylem conduits but distribute in the cortical and xylem resin canals (Mamiya, 1975;Ichihara et al, 2000). They can then move through the resin canals to reach almost all parts of the stem and branches fairly rapidly (Hashimoto and Kiyohara, 1973;Kuroda and Ito, 1992;Kuroda, 2008).…”
mentioning
confidence: 99%
“…The avirulent isolates have a lower potential to invade the bark tissues of pine shoots (Asai, 2002), and lower ability to disperse (Ichihara et al, 2000) and propagate (Kiyohara and Bolla, 1990) within healthy pine trees. The number of nematodes of avirulent isolates carried by the vector beetle, Monochamus alternatus Hope, is far fewer than that of the virulent isolates (Aikawa et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Hypotheses include cell death, cavitation and embolism caused as a result of increased production of volatile terpenes (Kuroda, 1991;Ikeda and Kiyohara, 1995;Ichihara et al, 2000). Regardless of the mechanism, the results of the current study showed all seven pine species and hybrids to be susceptible to PWN.…”
Section: Discussionmentioning
confidence: 56%